2007
DOI: 10.4321/s0004-06142007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del tabaquismo sobre la espermatogénesis en hombres con infertilidad idiopática

Abstract: The results show that tobacco alters sperm concentration and morphology with an increase of immature forms, demonstrating an altered spermatogenesis process. The consumption of tobacco should be evaluated to carry out the integral study of infertile man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In humans, it has been shown that cigarette smoke is able to alter sperm density, motility, morphology and seminal fluid leukocyte concentration. Effects of the cigarette smoke on sperm DNA integrity, aneuploidy rate, production of free oxygen radicals (ROS) have been evaluated, but the results of these studies appear conflicting: some have shown a negative effect (Stillman et al, 1986; Close et al, 1990; Pacifici et al, 1993; Sofikitis et al, 1995; Vine et al, 1996; Curtis et al, 1997; Rubes et al, 1998; Zhang et al, 2000; Saleh et al, 2002; Kunzle et al, 2003; Said et al, 2005; Sepaniak et al, 2006; Gaur et al, 2007; Reina Bouvet et al, 2007; Calogero et al, 2009; Chohan and Badawy, 2010; El-Melegy and Ali, 2011), while others reported no effect (Vogt et al, 1986; Dikshit et al, 1987; Oldereid et al, 1989; Lewin et al, 1991; Belcheva et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…In humans, it has been shown that cigarette smoke is able to alter sperm density, motility, morphology and seminal fluid leukocyte concentration. Effects of the cigarette smoke on sperm DNA integrity, aneuploidy rate, production of free oxygen radicals (ROS) have been evaluated, but the results of these studies appear conflicting: some have shown a negative effect (Stillman et al, 1986; Close et al, 1990; Pacifici et al, 1993; Sofikitis et al, 1995; Vine et al, 1996; Curtis et al, 1997; Rubes et al, 1998; Zhang et al, 2000; Saleh et al, 2002; Kunzle et al, 2003; Said et al, 2005; Sepaniak et al, 2006; Gaur et al, 2007; Reina Bouvet et al, 2007; Calogero et al, 2009; Chohan and Badawy, 2010; El-Melegy and Ali, 2011), while others reported no effect (Vogt et al, 1986; Dikshit et al, 1987; Oldereid et al, 1989; Lewin et al, 1991; Belcheva et al, 2004). …”
Section: Introductionmentioning
confidence: 99%